Invasive Haemodynamic Assessment Before and After Left Ventricular Assist Device Implantation: A Guide to Current Practice - Jesus Gonzalez; Paul Callan (Interventional Cardiology: Reviews, Research, Resources)
Mechanical circulatory support for the management of advanced heart failure is a rapidly evolving field. The number of durable long-term left ventricular assist device (LVAD) implantations increases each year, either as a bridge to heart transplantation or as a stand-alone ‘destination therapy’ to improve quantity and quality of life for people with end-stage heart failure. Advances in cardiac imaging and non-invasive assessment of cardiac function have resulted in a diminished role for right heart catheterisation (RHC) in general cardiology practice; however, it remains an essential tool in the evaluation of potential LVAD recipients, and in their long-term management. In this review, the authors discuss practical aspects of performing RHC and potential complications. They describe the haemodynamic markers associated with a poor prognosis in patients with left ventricular systolic dysfunction and evaluate the measures of right ventricular (RV) function that predict risk of RV failure following LVAD implantation. They also discuss the value of RHC in the perioperative period; when monitoring for longer term complications; and in the assessment of potential left ventricular recovery.